Benign Paroxysmal Positional Vertigo (BPPV) (Oshada, 2025)
Benign Paroxysmal Positional Vertigo (BPPV) is a common peripheral vestibular disorder, particularly in elderly women, characterized by brief vertigo attacks caused by changes in head position. This study aims to present a comprehensive clinical review of the etiology, pathophysiology, diagnosis, and non-pharmacological and pharmacological management of BPPV. Using a descriptive qualitative approach based on a literature review, this study analyzed selected literature sources from 2019 to 2024. The results indicate that the primary mechanism of BPPV is the displacement of otoconia from the utricle into the semicircular canals, causing vertigo through abnormal stimulation of the vestibular system. Diagnosis is confirmed through provocative maneuvers such as the Dix-Hallpike and Supine Roll Tests. Primary management includes the Epley maneuver, Semont, and Brandt-Daroff exercises, which have proven effective and safe, even for self-administration at home. Pharmacological therapy is only given to relieve acute symptoms, while surgery is considered in refractory cases. This study emphasizes the importance of accurate diagnosis, appropriate mechanical therapy approaches, and patient education as key strategies for improving treatment success and preventing long-term recurrence. Integrating anatomical-physiological understanding with clinical application is key to everyday medical practice.